Pengaruh profitabilitas dan likuiditas terhadap peringkat obligasi - Rahim, Fahreza Gadjali (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
One form of funding that can be done by a company is by issuing bonds. This research was conducted with the aim of testing the significance of the influence of profitability and liquidity on bond ratings in the property, real estate and construction sectors. When investors are interested in buying bonds, there are several things they must pay attention to, one of which is the bond rating as a reference for the company's performance in paying its debts. The profitability bond rating is measured using the Return On Assets proxy, while liquidity is measured using the Current Ratio proxy and the rating agency used is PT Pefindo. Sampling was carried out by purposive sampling. The data analysis method uses multiple linear regression using Eviews 10. The research results simultaneously show that Profitability with the Return On Assets proxy has an effect and Liquidity with the Current Ratio proxy has an effect on bond ratings. Simultaneously Profitability and Liquidity influence bond ratings. So, it can be concluded that the higher the level of profitability and the lower the company's liquidity, the higher the bond rating will be.